A History of Israel. From the Beginnings to the Bar Kochba Revolt, AD 135 - Soggin, J. Alberto (1984)
Translated by John Bowden from the Italian Storia d'Israele, dalle origini alla rivolta di Bar-Kochba, 135 d.C. Brescia 1985. Casa Editrice Paideia; 357-367: Appendix 1: Conrad, Diethelm, An Introduction to the Archeology of Syria and Palestine on the Basis of the Israelite Settlement. 368-383: Appendix 2: Tadmor, Hayim, The Chronology of the First Temple Period. A Presentation and Evaluation of the Sources